The Influence of Influencer Marketing, Fast Beauty and Buzzer on Purchase Decisions of Glad2Glow Among Female Management Students at Universitas Pembangunan Panca Budi 2022 - Nabila Aprilia; Ocdy Amelia; Slamet Widodo (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the influence of Influencer Marketing, Fast Beauty and Buzzer on the purchase decisions of Glad2Glow products among female students of the Management Study Program, Class of 2022, at Universitas Pembangunan Panca Budi. This research employs a quantitative approach with purposive sampling technique, involving 73 respondents drawn from a total population of 268 active female students. Data were collected through a structured questionnaire and analyzed using multiple linear regression with the assistance of SPSS version 20, encompassing validity and reliability tests, classical assumption tests, hypothesis testing (t-test and F-test), and the coefficient of determination (R²). The findings reveal that Influencer Marketing (X1) has a positive and significant effect on purchase decisions, with a t-value of 6.511 (sig. 0.000). Fast Beauty (X2) similarly demonstrates a positive and significant effect, with a t-value of 8.112 (sig. 0.000). Likewise, Buzzer (X3) exhibits a positive and significant effect, with a t-value of 7.405 (sig. 0.000). Simultaneously, all three variables exert a significant effect on purchase decisions, yielding an F-value of 53.817 (sig. 0.000). The R-Square value of 0.701 indicates that the three variables collectively account for 70.1% of the variation in purchase decisions. These results suggest that influencer-based digital marketing strategies, fast beauty trends, and buzzer activities are critical factors that substantially drive the purchase decisions of young consumers toward Glad2Glow beauty products.